Gamification on Cybersecurity Awareness Training for Adolescents: A Systematic Literature Review - Wijanarko, Andang; Erlansari, Aan (CV. Cendekiawan Muda Sriwijaya, 2025)
This systematic literature review aims to synthesize empirical evidence on the effectiveness, gamification elements, and implementation challenges of gamification in cybersecurity awareness training for adolescents. This study follows the PRISMA guidelines with a literature search on the Scopus academic database. Of the 124 studies identified, 14 studies met the inclusion criteria for further analysis. The synthesis results show that gamification significantly increases engagement, intrinsic motivation, and knowledge retention among adolescents on the topic of cybersecurity. The most effective gamification elements are points, badges, and leaderboards (PBL). However, key challenges such as framework usage, ensuring long-term engagement, and integration between game mechanics and learning outcomes must be considered for future research.